Educational achievement and gender differences : the role of the interaction between emotional stability and conscientiousness - Wehner, Caroline [Verfasser]; Schils, Trudie [Verfasser] (My University, 2019)
"The personality traits emotional stability and conscientiousness as well as the concept of gender are known to be predictive of educational achievement. Nevertheless, the interaction between these two traits and their relationship with both educational achievement and gender heterogeneity therein are far less explored and understood. We addressed this issue by using rich data from the British Cohort Study 1970 (BCS70) to targeting the relationship between personality as measured in adolescence and educational achievement in adulthood. We found that emotional stability was positively related to education outcomes for females, while conscientiousness was able to further boost their educational achievement. By contrast, these findings also indicated that less emotional stability was positively related to education outcomes for conscientious males. Our results suggest that an isolated examinations of the relationship between either emotional stability or conscientiousness and educational achievement while neglecting gender heterogeneity within these relations is likely misleading." (Authors' abstract, BIBB-Doku)
Keywords: S 4.3.6 Human Capital; T 4.6 Wirtschafts- und Rechtswissenschaften; G 1.3.3.1 Qualifikationsverwertung; T 4.2 Psychologie; T 3.5 Statistik; I 2.2.1 Westeuropa; Humankapital; Bildungsökonomie; Bildungsaspirationen; Geschlechterdifferenz; Einflussfaktor; Persönlichkeitsmerkmal; Emotionalität; Gewissenhaftigkeit; Langzeitstudie; Längsschnittuntersuchung; Großbritannien